Home care in COVID-19 patients with the home-quarantined condition: A study from Iran - Poorandokht Afshari; Maryam Beheshti-Nasab; Elham Maraghi; Simin Sadeghi; Nafiseh Sanjari; Kourosh Zarea (Frontiers Media S.A., 2022)
ObjectivesDuring the COVID-19 home-quarantines, home care services may act as an auxiliary component of health care system, which reduces the burden on the formal health care system. This study aimed to investigate the status of informal home care provided for home quarantined patients with COVID-19 in southwest Iran.MethodsThis descriptive study was conducted on 288 patients with COVID-19 in Ahvaz (southwest Iran). Inclusion criteria included a known case of COVID-19, willingness to participate in the study, recommendation of home quarantine from a health center, having a smartphone, and fluency in reading and writing in Persian, and the exclusion criterion was a history of COVID-19 longer than 3 months. The data collection method was structured interviews based on a questionnaire (face-to-face-telephone calls-video call). SPSS software was used for the analysis of data.Results45.5% of the participants in the study were women with a mean age of 37.82 (10.48%) and 55.5% were men with a mean age of 36.12 (11.93%). Findings showed that in most cases, the spouse (61.4) is responsible for the care of the patient, and in other cases, parents are responsible for this duty. 57.3% of the patients stated that they themselves had to leave home to provide for necessities of life, and 37.2% stated that they were in charge of cooking. 47.9% of the patients evaluated the quality of quality of care provided at home as good. Most of patients and caregivers referred to hospital for getting information (35.8% patients and 34% caregivers). Most of patients recovered from diseases (60.8%) and 39.2% were hospitalized. Although 43.9% of men and 33.6% of women were hospitalized and a there was a significant difference between men and women (P < 0.04).ConclusionDuring COVID-19 pandemic home care to reduce the burden on the health system are very important. We must also know that this type of care requires informed and planned support and sufficient community education. The health care system needs to put self-care and family care among its top priorities. The focus should be on educational and mental support of informal caregivers along with measures that protect their relatives from COVID-19.